Microscopic Analysis of the Tupanvirus Cycle in Vermamoeba vermiformis - Silva, Lorena C. F.; Rodrigues, Rodrigo Araújo Lima; Oliveira, Graziele Pereira; Dornas, Fabio Pio; La Scola, Bernard; Kroon, Erna G.; Abrahão, Jônatas S. (Frontiers in Microbiology, 2019)
Since Acanthamoeba polyphaga mimivirus was identified in 2003, several other giant viruses of amoebae have been isolated, highlighting the uniqueness of this group. In this context, the tupanviruses were recently isolated from extreme environments in Brazil, presenting virions with an outstanding tailed structure and genomes containing the most complete set of translation genes of the virosphere. Unlike other giant viruses of amoebae, tupanviruses present a broad host range, being able to replicate not only in Acanthamoeba sp. but also in other amoebae, such as Vermamoeba vermiformis, a widespread, free-living organism. Although the tupanvirus cycle in Acanthamoeba castellanii has been analyzed, there are no studies concerning the replication of tupanviruses in other host cells. Here we present an in-depth microscopic study of the replication cycle of tupanvirus in V. vermiformis. Our results reveal that tupanvirus can enter V. vermiformis and generate new particles with similar morphology to when infecting A. castellanii cells. Tupanvirus establishes a well-delimited electron-dense viral factory in V. vermiformis, surrounded by lamellar structures, which appears different when compared with different A. castellanii cells. Moreover, viral morphogenesis occurs entirely in the host cytoplasm within the viral factory, from where complete particles, including the capsid and tail, are sprouted. Some of these particles have larger tails, which we named “supertupans”. Finally, we observed the formation of defective particles, presenting abnormalities of the tail and/or capsid. Taken together, the data presented here contribute to a better understanding of the biology of tupanviruses in previously unexplored host cells.